Development, predictors, and effects of trainees’ organizational identification during their first year of vocational education and training - Maué, Elisabeth; Findeisen, Stefanie; Schumann, Stephan (Frontiers in Psychology, 2023)
The vocational identity of trainees is one component of their professional competence and is considered to be a central goal of vocational education and training (VET) programs. From the numerous identity constructs and conceptualizations, this study focuses on the organizational identification of trainees, that is, the extent to which trainees internalize the values and goals of their training company and perceive themselves as part of this company. We are specifically interested in the development, predictors, and effects of trainees’ organizational identification, as well as the interrelations between organizational identification and social integration. We use longitudinal data of n = 250 trainees in dual VET programs in Germany at the very beginning of their VET program (t1), after three months (t2), and after nine months (t3). A structural equation model was used to analyze the development, predictors, and effects of organizational identification for the first nine months of training and the cross-lagged effects between organizational identification and social integration. The results showed a high stability of trainees’ organizational identification over the first nine months. Regarding the predictors, the results indicated positive direct and indirect effects of the formal socialization tactics implemented by the training company, as well as of support by the trainer at the beginning of the training. However, collegial support at the beginning of the training did not seem to play a significant role in organizational identification. Moreover, organizational identification positively affected trainees’ emotional engagement and self-perceived competence while negatively predicting dropout intentions after nine months of training. Finally, the cross-lagged effects between organizational identification and social integration were not significant, and only at t3 were these constructs positively correlated. However, regarding the development, predictors, and effects, very similar results were found for organizational identification and social integration. The results underline the positive significance of organizational identification for the individual, the company, and society, even at this early stage of training. The results are discussed regarding both their scientific and practical implications.